ARCHIVES OF THE RUSSIAN FEDERATION CONCERNING HISTORY OF THE MOSCOW INSTITUTE OF NATIONAL ECONOMY - Stanislav A. Ruzanov (Вестник Российского экономического университета имени Г. В. Плеханова)
On the basis of source analysis of archive documents the author studies work of the Moscow Plekhanov Institute of National Economy during the most difficult period of institution history and history of Russian higher education in general, i. e. the pre-war time from mid- late- 1930s of the 20th century. He raises the question of the faculty and employees functioning as well as the institution management, its directors M. I. Lacis, A. K. Abolin, A. V. Morozov. The author points out the necessity to highlight contribution of the Plekhanov Russian University of Economics academics to the process of establishing and developing the Russian state system, public, political and cultural life of the country at various stages of its history.